Identification and characterization of the RAD51 gene from the ciliate Tetrahymena thermophila. - Campbell, C (1998)
The RAD51 gene is a eukaryotic homolog of rec A, a critical component in homologous recombination and DNA repair pathways in Escherichia coli . We have cloned the RAD51 homolog from Tetrahymena thermophila , a ciliated protozoan. Tetrahymena thermophila RAD51 encodes a 36.3 kDa protein whose amino acid sequence is highly similar to representative Rad51 homologs from other eukaryotic taxa. Recombinant Rad51 protein was purified to near homogeneity following overproduction in a bacterial expression system. The purified protein binds to both single- and double-stranded DNA, possesses a DNA-dependent ATPase activity and promotes intermolecular ligation of linearized plasmid DNA. While steady-state levels of Rad51 mRNA are low in normally growing cells, treatment with UV light resulted in a >100-fold increase in mRNA levels. This increase in mRNA was time dependent, but relatively independent of UV dose over a range of 1400-5200 J/m2. Western blot analysis confirmed that Rad51 protein levels increase upon UV irradiation. Exposure to the alkylating agent methyl methane sulfonate also resulted in substantially elevated Rad51 protein levels in treated cells, with pronounced localization in the macronucleus. These data are consistent with the hypothesis that ciliates such as T.thermophila utilize a Rad51-dependent pathway to repair damaged DNA.